(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to build a training program based on comprehensive quality standards to develop the teaching competencies of art education teachers in primary schools, and then measure the size of its impact on the development of teaching competencies.The researcher relied on the experimental method and on the experimental design with partial control and the group (experimental and control) with the application of a pre and post test.Where the research sample consisted of (60) male and female teachers of art education in primary schoolswhere the control group consisted (30) male and female teachers and tge experimental (30) male and female teachers who are on the staff of the general directorate of diyala education The researcher has prepared two tools for the current research, namely 1- the cognitive test to measure teaching competencies, which consisted of (20) items. 2- the skill test tool(observation form according to the Stanford five – point scale) to observe and evaluate art education teachers in teaching competencies (cognitive –performance – and interactive – and productivity ) the observation form consisted of (65) paragraphs The researcher verified the validity and reliability of the two research tools by presenting them to a group of experts and lawyers , so that the two tools became valid for application to the research sample . Among the most important results of the current research: 1- the size of the effect left by the training program for art education teachers in the experimental group appeared (0,44) in the post –cognitive test, which is a high level and was conducted in favor of the experimental group and indicates the effect of the training program in developing the aspect the cognitive . 2- the size of the effect left by the training program for the teachers of art education in the experimental group appeared(0,986 ) in the post-total skill test, which is a high and significant level in favor of the experimental group and indicates the effect of the training program in developing their teaching competencies 3- there are statistically significant differences when significance level (0.05) between the experimental and control group in the post cognitive test in favor of the experimental group 4- there are statistically significant differences at the level of significance (0,05) between the experimental and control group in the total post skill test in favor of the experimental group In light of the results and results and conclusions of the research, the researcher recommended the following : 1- adopting the program prepared for this research in training art education teachers within in courses held by the ministry of education 2- doing more studies on comprehensive quality standards because of their impact on developing and improving all aspects of the educational and educational process . 3- The researcher attributes the experimental groups superiority in performance sufficiency to the fact that it includes most of the teachers behavior in the classroom. At the conclusion of the current research , the researcher suggested the following : 1- building training programs according to the comprehensive quality standards for all scientific disciplines 2- conducting a study within a training program that studies each adequacy separately.